2020
DOI: 10.1007/s00049-020-00335-z
|View full text |Cite
|
Sign up to set email alerts
|

Rectal gland exudates and emissions of Bactrocera bryoniae: chemical identification, electrophysiological and pheromonal functions

Abstract: Bactrocera bryoniae is a polyphagous and economically significant fruit fly found in Indonesia, Papua New Guinea and Australia. To understand chemical-mediated sexual communication, and the potential for novel pheromone-based attractants for monitoring and mass-trapping of B. bryoniae, rectal gland exudates and emissions from sexually mature males and females were investigated. Gas chromatography-mass spectrometry showed that male rectal glands contained six compounds, of which 1,7-dioxaspiro [5,5]undecane eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…The major compounds ethyl dodecanoate ( 19 ) and ethyl tetradecanoate ( 25 ) in the present study have also been reported as the major constituents of the rectal glands and headspace volatiles of females in several other Bactrocera [ 8 , 22 , 23 , 26 , 34 ]. The esters of saturated/unsaturated fatty acids and several acids are female specific and have also been reported in other Bactrocera species but in different proportions in each species [ 8 , 22 , 23 , 24 , 26 , 34 , 35 , 36 ]. Interestingly, ethyl dodecanoate ( 19 ) comprised 39.1% in rectal gland samples but 70.2% in headspace samples.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The major compounds ethyl dodecanoate ( 19 ) and ethyl tetradecanoate ( 25 ) in the present study have also been reported as the major constituents of the rectal glands and headspace volatiles of females in several other Bactrocera [ 8 , 22 , 23 , 26 , 34 ]. The esters of saturated/unsaturated fatty acids and several acids are female specific and have also been reported in other Bactrocera species but in different proportions in each species [ 8 , 22 , 23 , 24 , 26 , 34 , 35 , 36 ]. Interestingly, ethyl dodecanoate ( 19 ) comprised 39.1% in rectal gland samples but 70.2% in headspace samples.…”
Section: Discussionsupporting
confidence: 74%
“…Although less common, aromatic compounds are also found in Zeugodacus cucurbitae [ 15 ]. The most commonly reported compound in Bactrocera and Zeugodacus rectal gland secretions is ( E , E )-2,8-dimethyl-1,7-dioxaspiro[5.5]undecane [ 8 , 15 , 16 , 19 , 20 , 22 , 23 , 24 , 25 , 26 ]. This compound is also known to occur in other insects, such as Polistes wasps and Ontholestes beetles [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the disproportionately high number of female-biased compounds that are long-Rt suggests that some of those compounds could be involved in shorter range communication. The potential pheromonal function of identified compounds can now be tested in laboratory and field enclosure assays of Qfly behaviours associated with mate attraction and choice [ 18 , 94 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report for the first time the release, and the electroantennographic and behavioral activity, of olean on both sexes of the FOB. This spiroacetal compound has been previously detected only in fruit fly species (Diptera: Tephritidae), and in the stingless bee Partamona cupira (Smith) (Hymenoptera: Apidae) [36][37][38]. Biologically active spiroacetals have been also described as part of the pheromonal communication system of some bark beetles (Coleoptera: Curculionidae), such as (2S,5S)-chalcogran [(2S,5S)-2-ethyl-1,6-dioxaspiro [4.4]nonane] in the genus Pityogenes Bedel [39][40][41], and (5S,7S)-conophthorin [(5S,7S)-7-methy1-1,6-dioxaspiro [4.5]decane] in Pityophthorus carmeli Swaine [42], among others.…”
Section: Discussionmentioning
confidence: 99%